A-to-I RNA editing independent of ADARs in filamentous fungi. Issue 10 (2nd October 2016) - Wang, Chenfang; Xu, Jin-Rong; Liu, Huiquan
ABSTRACT: ADAR mediated A-to-I RNA editing is thought to be unique to animals and occurs mainly in the non-coding regions. Recently filamentous fungi such as Fusarium graminearum were found to lack orthologs of animal ADARs but have stage-specific A-to-I editing during sexual reproduction. Unlike animals, majority of editing sites are in the coding regions and often result in missense and stop loss changes in fungi. Furthermore, whereas As in RNA stems are targeted by animal ADARs, RNA editing in fungi preferentially targets As in hairpin loops, implying that fungal RNA editing involves mechanisms related to editing of the anticodon loop by ADATs. Identification and characterization of fungal adenosine deaminases and their stage-specific co-factors may be helpful to understand the evolution of human ADARs. Fungi also can be used to study biological functions of missense and stop loss RNA editing events in eukaryotic organisms.